Space, Alterity, Identity, and Violence: The Horizontal and the Vertical in Views of the Turkish Enemy during the Sixteenth and Early Seventeenth Century - Perceval, José María (Eikón / Imago, 2020)
The aim of this paper is to study the process of creation of the image of the Turk in literary and visual sources, specially during 16th and 17th centuries. This process is studied taking into account the presence of conversos (Moriscos) in the Iberian Peninsula and how this fact was important in the configuration and perception of the otherness in that moment, as well as the construction of the identity.